Hasil Belajar Sejarah Siswa Dengan Media Pembelajaran Kung Fu Quiz Pada Kelas XI SMA Negeri 8 Banda Aceh - Safina Zuhra (Sociale : Journal of Social Science, 2026)
This study aimed to determine the history learning outcomes of Grade XI students after learning through the Kung Fu Quiz learning media at SMA Negeri 8 Banda Aceh. This research employed a quantitative approach using a Pre-Experimental Design with a One-Shot Case Study design, involving only one experimental group. The population consisted of all Grade XI students of SMA Negeri 8 Banda Aceh, comprising eight classes. The sample was Class XI A2-4, which initially consisted of 36 students. However, only 28 students participated in the entire research process; therefore, the data analysis was based on 28 students. The sample was selected using purposive sampling. Data were collected through observation, tests, and documentation. The results showed that the students' mean history learning outcome after using the Kung Fu Quiz learning media was 78.57, which was higher than the school's MMC of 70. The One-Sample t-test yielded a t-value of 3.422, which exceeded the t-table value of 1.703 at the significance level of α = 0.05 (3.422 > 1.703). In addition, the one-tailed significance value was 0.001, indicating that the students' mean learning outcome was significantly higher than the established MMC. Therefore, it can be concluded that the Kung Fu Quiz learning media was effective in helping Grade XI A2-4 students at SMA Negeri 8 Banda Aceh achieve mastery in history learning outcomes.